Discovering Aberrant Patterns of Human Connectome in Alzheimer's Disease via Subgraph Mining - Junming Shao; Qinli Yang; Wohlschlaeger, A.; Sorg, C. (2012 IEEE 12th International Conference on Data Mining Workshops, 2012)
Alzheimer's disease (AD) is the most common cause of age-related dementia, which prominently affects the human connectome. Diffusion weighted imaging (DWI) provides a promising way to explore the organization of white matter fiber tracts in the human brain in a non-invasive way. However, the immense amount of data from millions of voxels of a raw diffusion map prevent an easy way to utilizable knowledge. In this paper, we focus on the question how we can identify disrupted spatial patterns of the human connectome in AD based on a data mining framework. Using diffusion tractography, the human connectomes for each individual subject were constructed based on two diffusion derived attributes: fiber density and fractional anisotropy, to represent the structural brain connectivity patterns. Then, these humanconnectomes were further mapped into a series of unweighted graphs by discretization. After frequent sub graph mining, the abnormal score was finally defined to identify disrupted sub graph patterns in patients. Experiments demonstrated that our data-driven approach, for the first time, allows identifying selective spatial pattern changes of the human connectome in AD that perfectly matched grey matter changes of the disease. Our findings further bring new insights into how AD propagates and disrupts the regional integrity of large-scale structural brain networks in a fiber connectivity-based way.